1982
DOI: 10.1271/bbb1961.46.2477
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of sclareol.

Abstract: The microbial transformation of sclareol, a tobacco constituent, by a soil bacterium JTS-162 was studied. Manool, manoyl oxide and a new compound; 14,15-dinorlabd-8(17)-en-13-one were isolated from the culture broth as transformation products. In the presence of metabolic inhibitors such as a,a'-dipyridyl, a compound; labda-8(17),14-dien-1 3/?,18-diol and two new compounds; 13/5hydroxylabda-8(17), 14-dien-18-al and 13/?-hydroxylabda-8(17),14-dien-18-oic acid were accumulated in the culture broth as transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The phytochemical investigation of the hexane extract from the leaves of X. laevigata (Annonaceae) yielded six compounds (Figure 1), including one uncommon ent-kaurene diterpenoid ent-7β-acetoxy-16β-hydroxy-kaurane (3), in addition to other five isolated compounds, abieta-7,13-dien-3-one (1), 26 spathulenol (2), 24 13-hydroxy-ent-labda-8,14-dien-18-oic acid (4-epi-cupressic acid) (4), 27 (−)-kaurane-7β,16α-diol (powerol) (5), 28 and 8,20-epoxy-13-hydroxy-ent-labda-14-en-18-oic acid (labdorffianic acid B) (6). 29 Compound 3 was obtained as a white amorphous powder with the molecular formula C 22 25 The signals at δ H 2.05 (s, 3H) and δ H 4.62 (dd, J = 2.8 and 2.9 Hz, 1H) revealed the presence of an acetoxy group and an oxygenated carbon in the structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytochemical investigation of the hexane extract from the leaves of X. laevigata (Annonaceae) yielded six compounds (Figure 1), including one uncommon ent-kaurene diterpenoid ent-7β-acetoxy-16β-hydroxy-kaurane (3), in addition to other five isolated compounds, abieta-7,13-dien-3-one (1), 26 spathulenol (2), 24 13-hydroxy-ent-labda-8,14-dien-18-oic acid (4-epi-cupressic acid) (4), 27 (−)-kaurane-7β,16α-diol (powerol) (5), 28 and 8,20-epoxy-13-hydroxy-ent-labda-14-en-18-oic acid (labdorffianic acid B) (6). 29 Compound 3 was obtained as a white amorphous powder with the molecular formula C 22 25 The signals at δ H 2.05 (s, 3H) and δ H 4.62 (dd, J = 2.8 and 2.9 Hz, 1H) revealed the presence of an acetoxy group and an oxygenated carbon in the structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to previously published literature data, 28 only some 1 H NMR resonances were described for this compound, which enabled us to extensively revise 1D and 2D NMR data and unequivocally assign the chemical shifts of hydrogen and carbon atoms (Table 1), and its relative configuration. The isolated compounds: abieta-7,13-dien-3-one (1), 26 spathulenol (2), 24 13-hydroxy-ent-labda-8,14-dien-18-oic acid (4), 27 (−)-kaurane-7β,16α-diol (5), 28 and 8,20-epoxy-13-hydroxy-ent-labda-14-en-18-oic acid (6) 29 were identified by comparison of their NMR and MS data with those previously reported in the literature. Nevertheless, compounds 1, 4, and 6 have been described a long time ago and their published NMR data was incomplete ( 1 H and 13 C NMR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…restricta JTS-162. In the sclareol transformation by the same bacterium, 5) it was indicated that the addition of some metabolic inhibitors, such as o^a'-dipyridyl, was useful for the accumulation of new transformation products. In this study, we applied this method for the transformation of c/s-abienol to obtain new transformation products.…”
Section: Discussionmentioning
confidence: 99%
“…The extract was analysed by TLC and GC-MS. 17,14-dien-18-oic acid] were obtained as the transformation products from sclareol with bacterium JTS-162. 2 ) Ten mg of each compound (cisabienol, sclareol or their transformation products) was added to 5 ml of medium-A or medium-B containing the cured strain (about 108/ml) and 0.5mg of Tween-60. After 60 hr incubation, the resulting culture was acidified to pH 3.0 and extracted with ethyl acetate.…”
Section: Determination Of Dl-diaminopimelic Acid (Meso-dap)mentioning
confidence: 99%